2019
DOI: 10.1002/bjs.11388
|View full text |Cite
|
Sign up to set email alerts
|

Low-fat/high-fibre diet prehabilitation improves anastomotic healing via the microbiome: an experimental model

Abstract: Background: Both obesity and the presence of collagenolytic bacterial strains (Enterococcus faecalis) can increase the risk of anastomotic leak. The aim of this study was to determine whether mice chronically fed a high-fat Western-type diet (WD) develop anastomotic leak in association with altered microbiota, and whether this can be mitigated by a short course of standard chow diet (SD; low fat/high fibre) before surgery.Methods: Male C57BL/6 mice were assigned to either SD or an obesogenic WD for 6 weeks fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 37 publications
0
34
2
Order By: Relevance
“…Enterococcus faecalis is associated with an increased rate of anastomosis insufficiency, and second-and thirdgeneration cephalosporins failed to eradicate E. faecalis from anastomotic tissue [54]. In addition, there was a positive effect on anastomosis healing by a low-fat/high-fibre diet in a murine model, which was attributed, among other things, to an improved diversity of the intestinal microbiome [55]. The positive effect of SCFAs was also demonstrated in animal models.…”
Section: Discussionmentioning
confidence: 93%
“…Enterococcus faecalis is associated with an increased rate of anastomosis insufficiency, and second-and thirdgeneration cephalosporins failed to eradicate E. faecalis from anastomotic tissue [54]. In addition, there was a positive effect on anastomosis healing by a low-fat/high-fibre diet in a murine model, which was attributed, among other things, to an improved diversity of the intestinal microbiome [55]. The positive effect of SCFAs was also demonstrated in animal models.…”
Section: Discussionmentioning
confidence: 93%
“…A prospective study on 55 esophagectomy patients found a significantly greater variance in the microbiome diversity in oral and gastric samples of patients who had a leak compared to those without leaks (22). Also, a recent study found that lowfat/high fiber diet prehabilitation can reverse the adverse effect of a high-fat diet on anastomotic healing in mice by restoring the Bacteroidetes in the colonic lumen (23). If confirmed in larger studies, this may suggest that the oral and upper gastrointestinal microbiome are implicated in the pathogenesis of anastomotic leakage, and that manipulation of microbiome may possibly be used in the future to decrease the incidence of anastomotic leakage.…”
Section: Pathophysiology Of Anastomotic Healing and Prevention Of Leakagementioning
confidence: 99%
“…Given the numerous deletions, insertions and polymorphic regions between genomes in lower collagenolytic potential pre-op isolates and higher collagenolytic post-op isolates, it can be inferred that isolates represent distinct populations colonizing colonic tissues during surgery vs many days following surgery when present on a healing anastomotic wound. The high rate of colonization by collagenolytic strains that we previously observed on healing anastomotic wound several days after surgery [10,35,36] suggests that the healing anastomotic environment is a preferable niche for collagenolytic strains. Initial strains present on normal colonic tissue might represent a population of E. faecalis with varying levels of collagenolytic activity.…”
Section: Discussionmentioning
confidence: 78%